Variation in Presentation, Diagnosis, and Management of Children and Adolescents With ADHD Across European Countries. Issue 10 (August 2018) - Setyawan, Juliana; Fridman, Moshe; Grebla, Regina; Harpin, Valerie; Korst, Lisa M.; Quintero, Javier
Objective: To characterize differences in presentation, diagnosis, and management of children/adolescents with ADHD in six European countries.Method: Physicians abstracted clinical records for patients aged 6 to 17 years, diagnosed from 2004 to 2007 and treated for ≥2 years. Documentation included impairment due to core ADHD symptoms and additional ADHD symptoms/behaviors at diagnosis, diagnostic approach, and treatment modality.Results: Study included 779 patients treated by 340 physicians. Prevalence of ADHD subtypes (inattention, hyperactivity/impulsivity, or combined) was similar across countries. Mean scores for core and noncore symptom impairment varied and were highest in Italy and the United Kingdom. Variability was noted in diagnostic approach; 95% of physicians in the Netherlands used Diagnostic and Statistical Manual of Mental Disorders (4th edition) criteria versus 10% in Germany. Differences were reported for initial treatment modality, treatment switching, and physician-reported treatment outcomes.Conclusion: European countries varied in diagnostic approaches and practice management of children/adolescents with ADHD.